A Systematic Survey of Physicians' Insights Into Lipohypertrophy - Shen, Min; Shi, Yun; Zheng, Shuai; Fan, Hongqi; Xu, Jingjing; Yang, Tao (Frontiers in Public Health, 2021)
Background: It is important that physicians be aware of LH. We designed a questionnaire to determine physician awareness, knowledge, and behaviors regarding LH in clinical practice. Participants: A total of 499 questionnaires were completed by physicians in hospitals from 13 cities in Jiangsu Province, China. Key Results: Compared with physicians at tertiary hospitals, significantly fewer physicians at primary hospitals reported awareness of LH and its screening methods. The proportion of resident physicians aware of LH was significantly lower than the proportion of senior physicians. The proportion of physicians who could identify all LH risk factors among the low-GDP group was significantly higher than the high-GDP group. Only 38.7% of doctors could successfully identify all the hazards associated with LH, but more doctors in tertiary hospitals were able to do so compared to those in secondary and primary hospitals. Compared with tertiary hospitals, the proportions of primary and secondary hospitals with management processes were significantly lower. The proportion of doctors who educated patients regarding LH prevention and treatment in primary hospitals was markedly lower than in tertiary hospitals. Conclusions: Overall, physicians have an inadequate understanding of LH, especially in primary hospitals.